The Use of Schoology to Enhance Students’ Reading Comprehension at Lakidende University - Rama, Asri Nova; Rahim, Amiruddin; Alberth, Alberth (Halu Oleo University, 2018)
This study aimed to find out (1) the extent to which schoology enhance students’ reading comprehension (2) the students’ perception toward learning through shoology (3) the advantages of shoology for teaching reading comprehension (4) the disadvantages of shoology for teaching reading comprehension. This study was a mixed method research design known as explanatory mixed method design (Quan-Qual model). There were two groups involved namely experimental and control group. The study was carried out at Lakidende University of Unaaha with 40 undergraduates as the sample. Data were collected by using reading test and students’ self-diary. Moreover, the data were analyzed quantitatively and interpreted by using the software program of SPSS 16.0. the qualitative analysis was also conducted to analyze students’ self-diary. This study found that schoology give a significant enhancement on students’ reading comprehension from pre-test to post-test revealed the significant difference (0.008< 0.05) before and after the implementation of schoology. Based on students’ self-diary, it showed the students in experimental group gave positive responses toward schoology, the advantages of schoology for teaching reading comprehension were responsible, collaborative, ease of use and accessible while the disadvantages of schoology for teaching reading comprehension were the internet connection, time of the schoology and monotonous. This study concludes that schoology enhance students reading comprehension.